PERANCANGAN BISNIS MODEL PROBEET BAR FOR DIET AND MUSCLE GROWTH - Apriliyani, Apriliyani; Surya, Ferrianto; Ikhlas, Rendy; Hadylaw, Gabriel Chanfarry (Bina Nusantara University, 2014)
Business model is a form of a business plan or more commonly entitled a business plan. A good business models produces positive influences on the course of business thus this will impact the profit. This thesis aims to create an innovative business model on snacks made from tubers. The result from analysis such as journals and questionnaires showed that there this type of snack has business opportunity that can be developed. Business development Â of Healthy bar is very interesting because of the increasing number of people who put more attention on healthy snacks and communities lifestyle which increasingly refers not only health but also the appearance, such as women on diet and men practice fitness to shape body and muscles grows, and it was solely to get the ideal body. Besides innovation in the food business are currently being developed rapidly and become one alternative to compete in the snack food business.